In silico determination of fenthion, permethrin, and carbaryl as FFAR2 inhibitors: Type 2 diabetes mellitus pathomechanism study - Elly Nurus Sakinah; Nabil Athoillah; Komang Yunita Wiryaning Putri; Yunita Armiyanti (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: In the last few decades, many studies have shown that pesticides have a close relationship with increasing blood glucose levels and the incidence of diabetes. Some examples of pesticides include fenthion, permethrin, and carbaryl. Recently, free fatty acid receptor 2 (FFAR2) was identified as having a critical function in preventing insulin resistance. Activation of FFAR2 will reduce fat accumulation and induce glucagon-like peptide 1 (GLP-1) secretion, which plays an important role in regulating type 2 diabetes mellitus (T2DM) prevention.Objective: This study aims to determine a comparison of the binding ability between fenthion, permethrin, and carbaryl to FFAR2 protein for predicting the mechanism of pesticide toxicity to T2DM through an in silico study.Methods: This is an exploratory bioinformatic study. The protein structure was FFAR2 receptor (UniProt: O15552), while the ligand was fenthion (PubChem CID: 3346), permethrin (PubChem CID: 40326), and carbaryl (PubChem CID: 6129). This molecular docking was conducted in October 2022 using Asus X202XE with Intel® Core™ i3-3217U CPU equipped with BIOVIA Discovery Studio, AutoDockTools, and AutoDock Vina. Results: The binding affinity values generated after docking between fenthion, permethrin, and carbaryl with FFAR2 indicate that the binding affinity comparison is permethrin < carbaryl < fenthion. This explains that permethrin could form a stronger bond with FFAR2 protein than other pesticides. However, the visualisation results of the form of bond interactions show that permethrin does not bind to the active site of FFAR2, so it could not be called an inhibitor. This is different from fenthion and carbaryl, which could bind to several amino acid residues on the active site of FFAR2 and have the potential to become inhibitors.Conclusion: Carbaryl is a pesticide with the strongest FFAR2 inhibitor. Carbaryl could cause type 2 DM through its inhibitory pathway to FFAR2.